The Shortest Way to Modernity Is via the Margins: J.H. Prynne’s Later Poetry - Pietrzak, Wit (Text Matters: A Journal of Literature, Theory and Culture, 2012)
In the essay an attempt is made to investigate the processes of construction and reconstruction of meaning in the later books of the Cambridge poet J.H. Prynne. It has been argued that his poetry disturbs the act of meaning-making in a ceaseless experimental reconnection of words taken from multifarious discourses, ranging from economics to theology. Yet, what appears striking in this poetry is the fact that these lyrics take their force from figurative meaning with which the words are endowed in the process of a poem’s unfolding. Prynne appears to compose his lyrics by juxtaposing words that in themselves (or sometimes in small clusters) do yield a meaning but together exude an aura of unintelligibility. We may see this process as aiming at the destruction of what might be posited as the centre of signification of the modern language by constantly dispersing the meaning to the fringes of understanding. The poems force the reader to look to the margins of their meaning in the sense that the signification of the entire lyric is an unstable composite of figurative meanings of this lyric’s individual words and phrases. To approach this poetry a need arises to read along the lines of what is here termed “fleeting assertion”; it is not that Prynne’s poems debar centre in favour of, for instance, Derridean freeplay but rather that they seek to ever attempt to erect a centre through the influx from the margins of signification. Therefore they call for strong interpretive assertions without which they veer close to an absurdity of incomprehension; however, those assertions must always be geared to accepting disparate significatory influxes. Indeed, interpretation becomes a desperate chase after “seeing anew” with language but, at the same time, a chase that must a priori come to terms with the fact that this new vision will forever remain in the making.